The Assyrian Economic Impact on the Southern Levant in the Light of Recent Study - Younger, K. Lawson (2015)
In light of recent discussions concerning the impact of the Neo-Assyrian Empire in the Levant, this article investigates the growth and development of that empire's complex political, ideological and economic policies and practices. Based on this data, it seeks to evaluate recent scholarly proposals concerning Assyria's negative economic impacts in order to obtain a more comprehensive and balanced understanding.